2014
DOI: 10.1111/jbi.12370
|View full text |Cite
|
Sign up to set email alerts
|

The radiation of the clownfishes has two geographical replicates

Abstract: Aim The study of adaptive radiations provides an evolutionary perspective on the interactions between organisms and their environment, and is necessary to understand global biodiversity. Adaptive radiations can sometimes be replicated over several disjunct geographical entities, but most examples are found on island or in lakes. Here, we investigated the biogeographical history of the clownfishes, a clade of coral reef fish with ranges that now span most of the Indo‐Pacific Ocean, in order to explore the geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 46 publications
7
84
0
Order By: Relevance
“…Using phylogenies to disentangle the biogeographical histories of species is a complex task (Heads, ), and estimating the internal nodes of the phylogenies generated here proved difficult. Despite this, the analyses indicated that most of the models selected (7/9 analysis) included a founder‐event, which have been shown to be of prime importance in other island systems (Matzke, ; see Litsios, Pearman, Lanterbecq, Tolou, & Salamin, ; Pinheiro et al., and Wainwright et al., for examples). Overall, our biogeographical analyses show that dispersal and founder‐event speciation played a major role in the colonization of Rapa Nui.…”
Section: Discussionmentioning
confidence: 99%
“…Using phylogenies to disentangle the biogeographical histories of species is a complex task (Heads, ), and estimating the internal nodes of the phylogenies generated here proved difficult. Despite this, the analyses indicated that most of the models selected (7/9 analysis) included a founder‐event, which have been shown to be of prime importance in other island systems (Matzke, ; see Litsios, Pearman, Lanterbecq, Tolou, & Salamin, ; Pinheiro et al., and Wainwright et al., for examples). Overall, our biogeographical analyses show that dispersal and founder‐event speciation played a major role in the colonization of Rapa Nui.…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with our results, however, the lack of samples of A. akallopisos from the Maldives leaves the question open as to whether these two lineages of A. akallopisos meet at the Maldives as seems to be the case for the three anemone species in this study. Third, it has been shown that populations of the only anemonefish species present in Moorea (French Polynesia), Amphiprion chrysopterus , appear to be clearly different from populations elsewhere (Litsios, Pearman, Lanterbecq, Tolou, & Salamin, ). This coincides with our finding that the population of H. magnifica from Moorea is highly divergent from other H. magnifica populations.…”
Section: Discussionmentioning
confidence: 99%
“…We take advantage of an existing phylogeny of the clownfishes [21]. The dataset includes samples of 41 individuals representing 27 species of clownfish.…”
Section: Materials and Methods (A) Phylogenetic Reconstructionmentioning
confidence: 99%